Fabrication and characterization of FeCoNiCrMn, (Al) high entropy alloy based (Ti, Ta, Nb)(C, N) cermet. (December 2021) - Real, C.; Alcalá, M.D.; Trigo, I.; Fombella, I.; Córdoba, J.M.
Abstract: From nanostructured mechanically synthesized powder a set of FeCoNiCrMn, (Al) based (Ti, Ta, Nb)(C, N) cermets were fabricated and sintered by a pressureless procedure. Highly dense cermets were obtained, and the nature of chemical change, microstructure, mechanical properties and coarsening kinetic of ceramic phase were characterized by image analysis, microindentation, scanning electron microscopy and X-ray diffraction. The design of the material was performed using a set of three different chemical cermet composition and three different sintering temperatures, or comparative purposes. Graphical abstract: Unlabelled Image Highlights: A microhardness increment with temperature was observed for HEA without Al. Al presence favored phase segregation. Al presence favored formation of brittleness intermetallic compounds. A larger coarsening rate constant for the high entropy alloys with Al was observed. Coarsening can be seen regardless of the melting temperature of the binder.